Synthesising of flexural spindle head micro drilling machine tool in PLM environment. (14th December 2021) - Shinde, Sachin Manohar; Lekurwale, Ramesh R.
The advantage of building a machine in virtual environment helps in detection of the collision of the machine tool components with the work piece and effective process planning. Further every machine tool is virtually planned, designed and developed in product lifecycle management (PLM) platform before it is actually manufactured. This paper explains the synthesis of flexural spindle head used for micro drilling is in the PLM platform. The systematic procedure is adopted for validating the machine tool design in PLM environment. The first step deals with the hierarchy of assembly components that are designated using various possible kinematic chains. The second step involves assigning the required motions of the assembly components. The final step is the virtual control of the machine tool movements with the help of the virtual controller and respective post processor. On completion of all the steps the validation is carried out on the work piece.